Designing a Novel Reversible Systolic Array Using QCA - Mohammad Mahdi Abdollahi; Mohammad Tehrani (Ital Publication, 2017)
Many efforts have been done about designing nano-based devices till today. One of these devices is Quantum Cellular Automata (QCA). Because of astonishing growth in VLSI circuits Designs in larger scales and necessity of feature size reduction, there is more need to design complicated control systems using nano-based devices. Besides, since there is a critical manner of temperature in QCA devices, complicated systems using these devices should be designed reversibly. This article has been proposed a novel architecture for QCA circuits in order to utilizing in complicated control systems based on systolic arrays with high throughput and least power dissipation.